Multi-criteria evaluation of potential Australian tidal energy sites. (September 2021) - Marsh, Philip; Penesis, Irene; Nader, Jean-Roch; Cossu, Remo
Abstract: Most tidal energy site studies concentrate on resource size; few examine other factors that may be of equal or even greater importance in determining site feasibility for tidal turbine array deployments. These factors include aspects such as electrical grid proximity, water depth, the location of marine protected areas, pre-existing users, environmentally significant regions and other restrictions. Using these factors, a more holistic approach to site selection was conducted for Australian waters using a Multi-Criteria Evaluation (MCE) process. This MCE method uses standardized factors combined with weighted linear combinations to calculate a site suitability index, where each factor is multiplied by a weight of relative importance. A sensitivity analysis on the factor weighting was performed to ensure the suitable selection of weighting factors to reduce conformation bias. The developed MCE model identified three promising locations in Australia, with contiguous areas in regions to the north of Broome Western Australia of 534 km 2, the Banks Strait region northeast of Tasmania of 67 km 2, and the Clarence Strait located in the Northern Territory of <1 km 2 found. Additional examinations of possible co-location of tidal energy devices with wind and wave energy were examined. Highlights: Site suitability of potential Australian tidal energy sites determined nationally. Highly suitable areas identified near Broome and the Clarence and Banks Straits. Co-location with wave and wind renewable energy devices assessed.